Attitudes towards News Consumption on Online Media in the Era of Online Platform Communication - สาพิมพ์ เกศกนก; โอภารอิทธิวงษ์ วิภารัศม์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to study the attitude towards consuming news on online media in the 4.0 era of the population of Mueang Samut Prakan District, Samut Prakan Province, to study the efficiency of the attitude towards consuming news on online media of the population of Mueang Samut Prakan District, Samut Prakan Province, and to study the relationship between the attitude towards consuming news on online media in the 4.0 era and the efficiency of the attitude towards consuming news on online media of the population of Mueang Samut Prakan District, Samut Prakan Province. The population and sample consisted of 400 people from Mueang Samut Prakan District, Samut Prakan Province, Lat Krabang District, Bangkok. A simple random sampling was used. A questionnaire was used as the research tool. There were 3 parts: personal factors, attitude towards consuming news on online media in the 4.0 era, and efficiency of consuming news on online media, which had been tested for content consistency by experts. The questionnaire had a reliability value of .819. The statistics used in the study were percentage, mean, standard deviation, comparison of differences between 2 variables (Independent-Samples t-test), comparison of differences between more than 2 variables using analysis of variance. One-way Analysis of Variance (One-way Anova) and Pearson Correlation The research results can be summarized as follows: Categorized by gender, most respondents were female, accounting for 63.5 percent. Categorized by age, most respondents were 21-30 years old, accounting for 54.5 percent. Categorized by status, most respondents were single, accounting for 49.8 percent. Categorized by education level, most respondents had a bachelor’s degree, accounting for 40.7 percent. Categorized by salary level, most respondents had a salary level of more than 20,000, accounting for 45.5 percent.